Displaced Mexican American Workers in Retraining Programs - Diana P. Mena; Mary V. Alfred (Adult Education Research Conference, 2009)
One Stop Job Centers assist trade affected displaced workers in skills development and occupational retraining with the goal of re-incorporating them into the workforce. In this study, we explored the job loss and transitional experiences of two groups of low-literate, primarily Spanish speaking males. Findings included coping mechanisms and identification of barriers that included a failed method of instruction.